PENENTUAN KADAR TOTAL FENOLIK, TOTAL FLAVONOID DAN UJI AKTIVITAS ANTIOKSIDAN DARI EKSTRAK DAN FRAKSI DAUN KARAMUNTING (Rhodomyrtus tomentosa (Aiton) Hassk): antioxidant - Rahma Dona (Lembaga Penelitian Sekolah Tinggi Ilmu Farmasi Jl. Kamboja Simpang Baru-Panam, Pekanbaru, Riau 28293 Telp. (0761) 588006, Fax. (0761) 588007 e-mail: editor-jpfi@stifar-riau.ac.id, 2020)
Karamunting (Rhodomyrtus tomentosa (Aiton) Hassk) is a family of Myrtaceae which has been used by the community as traditional medicine. The purpose of this research is determine total phenolic and total flavonoid level and test antioxidant activity of Karamunting Leaves. Determination of total phenolic using gallic acid standard by the Folin Ciocalteu method. The results obtained total phenolic in water fraction of 99 mgGAE/g, ethanol extract 94,1 mgGAE/g, ethyl acetate fraction 83,3 mgGAE/g and n-hexane fraction 41,4 mgGAE/g. Determination of total flavonoid using standard quersetin with AlCL3 complex formation method, the results obtained total flavonoid in water fraction of 156,8 mgQE/g, ethanol extract 192,6 mgQE/g, ethyl acetate fraction 89,4 mgQE/g and n-hexane fraction 31,3 mgQE/g. Determination of antioxidant activity was determined by DPPH radical capture test (1,1-diphenyl-2-picrylhydrazyl), the results obtained in water fraction with IC50 value 15,02 µg/mL, ethanol extract 14,06 µg/mL, ethyl acetate fraction 14,48 µg/mL with very strong activity of antioxidant, whereas in the n-hexane fraction was categorized as weak antioxidant activity with an IC50 value of 264,02 µg/mL.